Understanding cognitive and socio-psychological factors determining farmers' intentions to use improved grassland: Implications of land use policy for sustainable pasture production. (March 2021) - Elahi, Ehsan; Zhang, Hongxia; Lirong, Xing; Khalid, Zainab; Xu, Haiyun
Highlights: The study estimates farmers' intention, barriers & drivers to use improved grassland. Theory of planned behavior determined farmers' intention to use improved grassland. Favorable attitude was found to use improved grassland, which is emerged from beliefs. Socioeconomic factors were the main barriers to not using improved grassland. Farmers were strongly encouraged by peer farmers & friends to use improved grassland. Abstract: The study aims to estimate farmers' intentions, barriers, and drivers to use improved grassland. In 2019, following a snowball sampling technique, 240 farmers from district Mansehra of Pakistan were interviewed using a well-structured questionnaire. During interviews, detailed questions were asked about socioeconomic variables, behavior belief, normative belief, and control belief. The theory of planned behavior (TPB) was used to determine farmers' cognitive and socio-psychological behavior to use improved grassland. Comparative to non-users, the grassland users were found with higher age, more education, large herd size, more milking animals, and milk yield. Factors such as large family size, higher dependency burden, less satisfaction from livestock farming, non-farm income, and lack of grassland ownership were the barriers to not using improved grassland in the study area. Path analysis confirmed that farmers who formed favourable attitudes to use improved grassland, had perceived strong social pressure. Moreover, they have had perceived difficulty and likely to believe that they control this behaviour and develop a firm intention to use improved grassland. A favorable attitude was found to use improved grassland, which is emerged from beliefs. Farmers were strongly agreed with statements that the improved grassland is beneficial for pasture availability throughout the year and to increase feed and milk production. Moreover, farmers were strongly encouraged by peer farmers and friends to use improved grassland, and they expressed a high degree of motivation to comply with the referents. Similarly, animal welfare concerns have positive while moral norms and self-identity negatively and significantly correlated with farmers' intention to use improved grassland. The estimated behavior belief, normative belief, and perceived behavior control significantly correlated with farmers' intention. While perceived difficulty negatively correlated with the intention. The study findings suggest to develop a proper framework of extension services to increase awareness of using improved grassland for sustainable pasture production.